Religious Involvement, Audience Demographics, and Media Bias - Glascock, Jack (Journal of media and religion, 2008)
This study sought to investigate the influence of religious involvement (religious partisanship, religiosity, and religious service attendance) as well as demographic factors (sex, ethnicity, and age) on the perception of media coverage of a controversial religious issue. Contrary to expectation none of the religious involvement measures were significant. However a significant effect for ethnicity on participants' perceptions of media bias was found. Several possible explanations, including issue salience, actual media bias, and acculturation, are discussed.